Thermal analysis and efficiency of an induction motor driven by a fault-tolerant multilevel inverter using FEM. Issue 2 (2nd March 2015) - Slawomir Wiak, Professor; Baptista, Bruno R. O.; Mendes, André M.S.; Cruz, Sérgio M.A.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a comparative study of the thermal behavior and efficiency of an induction motor fed by a fault-tolerant Three-Level Neutral Point Clamped (3LNPC) inverter, under normal conditions as well as after a post-fault reconfiguration, following an open-circuit fault in the inverter. For this purpose, a Matlab/Simulink model and three-phase induction motor models using a finite element method (FEM) software were developed. Besides, some experimental tests were conducted for different values of the induction motor load torque and speed reference to validate the models. Design/methodology/approach – To assess the thermal behavior and efficiency of the motor, electromagnetic and thermal models using a FEM software were developed. The coupling with the inverter drive is accomplished through a developed model in Matlab/Simulink which also includes the control system. The simulation tests were performed for a healthy and faulty inverter at different operating points of the three-phase induction motor. To validate the FEM models some experimental tests were performed. Findings – When the inverter operates in reconfigured mode the motor losses are higher and consequently temperature is higher and the motor efficiency is lower. The developed models are an alternative to a more detailed study of the motor when fed by a 3LNPC inverter and consequent optimization of the control system. Originality/value – With the developed tools, a better understanding of the motor behavior and performance is gained, allowing to forecast scenarios and optimize fault-tolerant control strategies for the drive.